2013
DOI: 10.1371/journal.pgen.1003844
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the Evolutionary Downside of CRISPR Immunity: Bacteria and Beneficial Plasmids

Abstract: The immune systems that protect organisms from infectious agents invariably have a cost for the host. In bacteria and archaea CRISPR-Cas loci can serve as adaptive immune systems that protect these microbes from infectiously transmitted DNAs. When those DNAs are borne by lytic viruses (phages), this protection can provide a considerable advantage. CRISPR-Cas immunity can also prevent cells from acquiring plasmids and free DNA bearing genes that increase their fitness. Here, we use a combination of experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
251
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(268 citation statements)
references
References 70 publications
15
251
2
Order By: Relevance
“…Targeting efficacy of the system appeared equivalent to other type II systems such as CRISPR1 and CRISPR3 from S. thermophilus (Barrangou et al, 2007). In agreement with previous studies, it was observed that spacer loss, likely through recombination between CRISPR repeats, is a major mechanism of preventing CRISPR-Cas interference (Jiang et al, 2013). Transformants exhibiting deletion of spacers likely incur a lower adaptive cost to the cell relative to mutations inactivating the CRISPR-Cas system as a whole.…”
Section: Mechanisms Of Escape From the Crispr-cas Systemsupporting
confidence: 86%
“…Targeting efficacy of the system appeared equivalent to other type II systems such as CRISPR1 and CRISPR3 from S. thermophilus (Barrangou et al, 2007). In agreement with previous studies, it was observed that spacer loss, likely through recombination between CRISPR repeats, is a major mechanism of preventing CRISPR-Cas interference (Jiang et al, 2013). Transformants exhibiting deletion of spacers likely incur a lower adaptive cost to the cell relative to mutations inactivating the CRISPR-Cas system as a whole.…”
Section: Mechanisms Of Escape From the Crispr-cas Systemsupporting
confidence: 86%
“…Our results strongly indicate that CRISPRCas targeting of these elements may influence chromosomal rearrangements and homeostasis. This finding is in contrast to experiments targeting essential features, which resulted in the selection of variants with inactivated CRISPR-Cas machinery (41). Mutation of essential ORFs is not a viable avenue for circumvention of CRISPR-Cas targeting, and thus only those clones with inactivated CRISPR-Cas systems remain.…”
Section: Discussionmentioning
confidence: 74%
“…A constitutive fitness cost of CRISPR-Cas systems could select for a loss of the systems in the absence of parasites (137). At present, the mechanistic basis for the observed fitness cost associated with the CRISPR-Cas system is unclear but may be related to autoimmunity (138)(139)(140)(141)(142)(143)(144) or allocation of resources to defense that would otherwise be invested in growth. Abortive infection.…”
Section: Fitness Costs Of Immunitymentioning
confidence: 99%